1992
DOI: 10.1002/jmri.1880020211
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative P‐31 MR spectroscopy of the liver in alcoholic cirrhosis

Abstract: To determine the cause of reduced urea synthesis in cirrhosis, absolute concentrations of phosphorus metabolites in the human liver have been measured in vivo with magnetic resonance (MR) spectroscopy. One-dimensional chemical shift imaging was used to obtain phosphorus-31 spectra from five healthy volunteers and five patients with alcoholic cirrhosis. A reference standard included in all studies enabled the calculation of absolute concentrations. In contrast to hepatic metabolite ratios, absolute concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
4
24
0
1
Order By: Relevance
“…[32][33][34][35][36][37] In addition to MRS-dependent differences, the great interindividual variability within and across these studies could be due to the nutritional status and variations of age and BMI. To overcome such influences, we controlled for dietary intake and matched the controls for age and BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35][36][37] In addition to MRS-dependent differences, the great interindividual variability within and across these studies could be due to the nutritional status and variations of age and BMI. To overcome such influences, we controlled for dietary intake and matched the controls for age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the high intraindividual and interobserver reproducibilities of ␥ATP and Pi made it possible to investigate more subtle changes in phosphorus metabolites across a range of hepatic insulin resistance and fat contents. 22 The decrease in absolute levels of ␥ATP in viral and alcoholic hepatitis 32,37 and obesity 38 has been commonly interpreted as "energy deficit" or impaired "ATP homeostasis". Decreased ␥ATP could result from hepatocellular ␥ATP depletion due to increased ATP utilization by energy-demanding processes such as Na ϩ /K ϩ adenosine triphosphatases, lipogenesis, or gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported good correlation with either an increased PME resonance or decreased PDE resonance in cirrhotic livers. [10][11][12][13][14][15][16][24][25][26][27][28][29] However, none has studied precirrhotic disease, apart from a relatively recent study by Kiyono et al 29 They found no correlation between the spectra obtained and histopathologic grading in a cohort of patients with either chronic viral hepatitis (hepatitis B or hepatitis C viruses) or autoimmune hepatitis. This study was flawed in that the etiology of the disease was not stratified properly and there was no clear or accepted histologic grading system used.…”
Section: Discussionmentioning
confidence: 99%
“…Even in this relatively small cohort, the sensitivity and specificity of this test for assessing disease severity approaches that reported in larger studies that used serum biochemical or extracellular matrix component markers for assessing fibrosis. 33 Previous studies have shown significant reduction in hepatic adenosine triphosphate levels with cirrhosis of differing disease etiology, 15,16 possibly related to reduced hepatic mass or differing hepatic bioenergetics in the cirrhotic liver, but subject numbers have been small. We, in contrast, did not find any significant change in MRmeasurable %adenosine triphosphate among the groups in our cohort of 48 patients with HCV-related liver disease, but most of our patients had precirrhotic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation